A Potential Polymorphism in the Promoter of Let-7 is Associated With an Increased Risk of Intracranial Aneurysm: A Case-Control Study. Issue 51 (December 2015) - Sima, Xiutian; Sun, Hong; Zhou, Peizhi; You, Chao
Abstract : Abstract: Let-7 family plays a key role in the progression of atherosclerosis and intracranial aneurysm (IA). We hypothesized that rs10877887 and rs13293512 polymorphisms in the promoters of let-7 family may be associated with the susceptibility of IA. We genotyped the 2 single nucleotide polymorphisms (SNPs) in 305 patients with IA and 401 healthy controls. The rs10877887 was analyzed using a polymerase chain reaction-restriction fragment length polymorphism assay, and the rs13293512 was analyzed using a TaqMan SNP genotyping method. The relative expression of let-7 family was measured in plasma of cases and controls using real-time PCR. We found that the rs13293512CT genotype was associated with a significantly increased risk of developing IA in a heterozygote comparison (adjusted OR = 1.43, 95% CI, 1.00–2.05, P = 0.048) and dominant comparison (adjusted OR = 1.44, 95% CI, 1.02–2.03, P = 0.04). Combined analysis showed that the rs10877887TT and rs13293512CC/CT genotypes had a significantly increased risk of IA (OR = 1.67, 95% CI, 1.04–2.68, P = 0.03). Moreover, the levels of let-7a, let-7d, and let-7f were downregulated in IA patients, and patients with the rs13293512CC/CT genotypes had a lower level of let-7a than those with rs13293512TT genotype ( P = 0.03). These findings indicate that the rs13293512CC/CT is a risk factor for the development of IA, possibly because of the genotypes resulting in a lower level of let-7a.